PHASEOLEAE (PAPILIONOIDEAE - LEGUMINOSAE) ON THE COAST OF AMAZONIA - Silva, MÃ´nica FalcÃ£o da (2015)
Leguminosae has a great importance in the formation of the vegetation and characterization of the Amazon sand coast. The Phaseoleae tribe at Para coastal sandbanks of is considered the most representative Leguminosae’s tribe. Therefore, the goal of this paper was the taxonomic treatment of these species. Botanical material from new collections and specimens from MG and IAN herbaria were analyzed. A total of 10 species were found and a taxonomic key, descriptions, geographic distribution, comments and illustrations were prepared to them. Among them, Clitoria laurifolia Poir., Dioclea guianensis Benth., Erythrina amazonica Krukoff e Mucuna pruriens (L.) DC. were new records to the study areas. The genus Clitoria was the most representative (2 spp.), and Centrosema brasilianum (L.) Benth. was the most common specie in the areas.Keywords: Clitoria; Centrosema brasilianum; sand coastal; morphology; taxonomy.